Pendampingan Asuhan Keperawatan Medikal Bedah pada Pasien dengan Gangguan Sistem Pernafasan (Asma) di Ruang Mawar RSUD Dr. Soekardjo Tasikmalaya - Acep Hidayatul Mustopa (Yayasan Inspirasi El Burhani, 2022)
Introduction: Asthma is a disease of the respiratory system in which inflammation or narrowing of the airway can occur repeatedly due to exposure to allergic agents and this condition can cause shortness of breath for sufferers. Asthma can be caused by predisposing factors such as genetics, as well as precipitating factors such as allergies, excessive exercise, bacterial infections of the respiratory tract, stress and weather changes. Objective: This assistance aims to provide nursing care to patients Br. B with a medical diagnosis of asthma in the Melati room at RSUD dr. Soekardjo Tasikmalaya in 2021. Method: Assistance activities are carried out by providing nursing care through 5 stages of the nursing process, including Assessment, Diagnosis, Nursing Intervention, Nursing Implementation, and Evaluation. Result: The results of the study found that the patient's main complaint was shortness of breath, the diagnosis that appeared in the patient was ineffective airway clearance, after being given nursing actions from October 6-8, the results obtained the patient said he was no longer short of breath, the patient was able to cough effectively, the patient was able to expel phlegm, Additional breath sounds are no longer audible, the patient is no longer taking nasal oxygen. Conclusion: After the process of providing nursing care was carried out from 06-08 October 2021, the nursing problems found in Br. B with a medical diagnosis of asthma can be resolved.